Project-Based Learning with Google Spreadsheets : An Effective Approach to Improving Student Learning Interest and Collaboration - Supriatiningtyas, Nurjannah; Maulida, Sri Agustina; Sucipto, Sucipto (Jurnal Paedagogy, 2025)
This study aims to measure the effectiveness of the use of the Project Based Learning (PjBL) learning model assisted by Google Spreadsheet in increasing students’ interest in learning and collaboration skills in Informatics subjects at SMKN 1 Arosbaya. The approach in this study is a quantitative with an experimental research type through a Quasi Experimental Design, namely Non-equivalent Control Group Design. In this design, both the experimental group and the control group are compared, although the group is selected and placed without going through random. The sample in this study was class X PHT B as the control class and class X PHT C as the experimental class with 35 students in each class. Hypothesis testing 1 and 2 using the independent sample t-Test, in hypothesis 1 it produces sig. 0.000 where H0 is rejected which means there is a significant influence between PjBL assisted by Google Spreadsheet on learning interest. Hypothesis testing 2 produces sig. 0.000 where H0 is rejected, which means that there is a significant influence between PjBL assisted by Google Spreadsheet on collaboration skills. In the hypothesis test 3 using the MANOVA test which shows a sig. level of 0.000 where the data shows that the significance level <0.05 then H0 is rejected, which means that there is a significant influence between PjBL assisted by Google Spreadsheet on learning interest and collaboration skills.